Types of Academic Dishonesty, Empathic Concern, and Peer Reporting Intention: Indonesian Students’ Perspective - Anna Armeini Rangkuti; Rahmadianty Gazadinda; Santi Yudhistira (STAI Hubbulwathan Duri, 2025)
Academic dishonesty remains a persistent issue in higher education, undermining academic integrity and fairness. Peer reporting is a potential deterrent; however, it is underutilized, particularly in collectivist cultures like Indonesia, where group cohesion is highly valued. This study investigates the types of academic dishonesty, levels of empathic concern, and students’ intentions to report a classmate’s misconduct. A survey was conducted among 228 Indonesian university students, assessing peer reporting intentions in response to two hypothetical scenarios—exam cheating and plagiarism. Empathic concern was measured using the Interpersonal Reactivity Index (IRI). Findings indicate significant differences in peer reporting intentions based on the type of academic dishonesty. Students were more inclined to report exam cheating than plagiarism (t = 10.545, p .001). Additionally, empathic concern negatively influenced the likelihood of reporting exam cheating (F = 7.572, p.05), suggesting that students with higher empathic concern were less likely to report misconduct. These findings underscore the need for universities to establish explicit policies and clear peer reporting procedures for all forms of academic dishonesty. Addressing students' empathic concerns when promoting ethical behavior is crucial in fostering a culture of academic integrity. Understanding the interplay between cultural values, academic dishonesty, and empathic concern is vital for designing effective interventions that encourage academic integrity in higher education.